Linear Quadratic Regulator-Based Coordinated Voltage and Power Control for Flexible Distribution Networks - Zhipeng Jing; Lipo Gao; Chengao Wu; Dong Liang (Energies)
Multi-port soft open points (SOPs) are effective devices for alleviating issues such as voltage violation and transformer overloading in distribution networks caused by the high penetration of distributed energy resources. This paper proposes a coordinated voltage and power control method for flexible distribution networks based on a linear quadratic regulator (LQR). First, the principle of coordinated voltage and power control is analyzed based on SOPs’ control strategies and a linear power flow model. Then, a discrete-time state-space model is constructed for flexible distribution networks with multi-port SOPs, using the voltage magnitude deviations at the AC side of all PQ-controlled voltage source converters (VSCs) and the loading rate deviations of the transformers corresponding to all PQ-controlled VSCs as state variables. An LQR-based optimal control model is then established, aiming to simultaneously minimize deviations of voltage magnitudes and transformer loading rates from their reference values, which correspond to the Vdc-controlled VSC. The optimal state feedback law is obtained by solving the discrete-time algebraic Riccati equation. The proposed method has been evaluated on two typical flexible distribution networks, and the simulation results demonstrate the effectiveness of the proposed control method in improving voltage profiles and alleviating transformer overloading conditions using local measurements and very limited communication. In specific situations, the imbalance of voltages and transformer loading rates among the interconnected feeders can be reduced by 40%.